Tracking 25 years of judo results from the World Championships and Olympic Games: Age and competitive achievement - Franchini, E.; Fukuda, D. H.; Lopes-Silva, J. P. (Journal of Sports Sciences, 2020)
We quantified the peak age of judokas during the World Championships (WC) and Olympic Games (OG) according to sex, weight category and competitive achievement and determined the relationship between competition year and athlete age. A retrospective study including 12,005 athletes who took part in the last 16 WC and 6 OG. Athletes were divided by sex, weight category and competitive achievement. Overall, females were younger than males, and older athletes competed at the OG compared to the WC. A weight category effect was also observed, with lighter athletes being younger than heavier athletes (p < 0.05). A competitive achievement effect was found for females, with athletes being defeated in the eliminatory phases being younger than those advancing further in the competitions (p < 0.05). Significant associations (p < 0.05) were shown between competition year and age category for males at the WC and for females at both the WC and OG. In general, lighter athletes are younger than heavier ones (p < 0.05). No difference in age was found between males concerning their competitive achievement in WC and OG, whereas younger females are defeated in the eliminatory phases (p < 0.05).